The Influence of Employee Empowerment and Public Service Motivation on Employee Performance Mediated by Work Discipline among the Employees of the City of Samarinda's Tax and Revenue Agency - Stefani jane Fonda; Sri Mintarti; Dirga Lestari (Cita Konsultindo Research Center, 2024)
Abstract The study aims to investigate the influence of employee empowerment and public service motivation on employee performance, mediated by work discipline, within the Regional Revenue Office (BAPENDA) of Samarinda City. The research follows a quantitative approach, utilizing Partial Least Squares (PLS) analysis as the statistical method and Structural Equation Modeling (SEM) as the conceptual framework. The research sample consisted of 120 employees from BAPENDA Samarinda. The results of this study indicate that employee empowerment and public service motivation have a positive impact on employee performance. Additionally, work discipline plays a significant mediating role in connecting employee empowerment and public service motivation to employee performance. These findings offer a valuable contribution to the understanding of human resource management in the public service sector, specifically within the context of the Regional Revenue Office. The implications of this research can assist organizations in enhancing employee performance through strategies that focus on employee empowerment and public service motivation, while recognizing the crucial role of maintaining work discipline as an effective mediating factor. This research also provides guidance for researchers and practitioners in developing more effective management models within the public service sector.